Thermal analysis of rubberwood - Tan A G; Scott J B (Journal of Natural Rubber Research, 1987)
The thermal behaviour of rubberwood in an inert environment was examined using differential thermal analysis (DTA). The resultant DTA trace contains a number of peaks, both endothermic and exothermic, attributed to degradation of the individual wood components. The effects of particle size of the wood, the gass flow rate, the heating rate and fungal infestation on the thermal response of the material were investigated. Reducing the gas flow rate has almost the same effect as increasing the particle size of the wood. A comparison was also made between the thermal behaviour of rubberwood and those of other wood species.
Keywords: Rubberwood